Docência universitária: narrativas de professores substitutos no IEAA/UFAM - Souza, Antônia Alves de (Brasil, 2021)
The work presented with the title “University teaching: narratives of substitute teachers at the IEAA/UFAM” had the look directed to substitute teachers in higher education who teach at the Institute of Education, Agriculture and Environment (IEAA). The research was carried out with five professors from different areas, who met the criteria for this study, which aimed to answer the following problem: What do professors narrate about the course in university teaching as substitute professors at the IEAA? In view of this concern, the research was outlined based on the general objective to understand the process of university teaching experienced by substitute professors who work in undergraduate and bachelor's degrees at the IEAA and, in the specific objectives: a) To analyze the perception of professors about teaching university; b) Identify the challenges of the participants, as substitute teachers, in relation to teaching and learning; c) Identify the knowledge of teaching evidenced by teachers in the exercise of the profession; d) Analyze the perception that teachers have about their pedagogical practices. The research is characterized by a qualitative approach, of the narrative type and the data collection technique was the narrative interview. From the analysis and interpretation of data, issues related to teaching and learning were highlighted in the narratives; to teacher and student interaction; the relationship between teachers and their peers; online classes that caused strangeness and distrust of their presence or absence in the classrooms; in addition to the feeling of not belonging to the course or the institution. We hope that this research will be an encouraging instrument for further research to involve substitute teachers in search of other answers and, thus, answer other questions that were not addressed in this study.